A physician-physiotherapist collaborative model in a family medicine teaching clinic - Simon Deslauriers (Canadian Medical Education Journal, 2018)
Persons with musculoskeletal disorders frequently seek care in family medicine clinics. However, musculoskeletal education provided in medical schools is often considered insufficient. The implementation of a collaborative model that integrates physiotherapists into teaching clinics may benefit the musculoskeletal training of medical residents. This paper describes a model developed in a family medicine teaching clinic by examining the interprofessional educational and collaborative activities implemented in this model. The model allowed to provide physiotherapy services, involve the physiotherapist in the training of family medicine residents and enhance interprofessional collaboration, particularly for the management of persons with musculoskeletal disorders. _____ Les personnes ayant des troubles musculosquelettiques consultent fréquemment en cliniques de médecine de famille. Cependant, l’enseignement musculosquelettique dispensé dans les programmes de médecine est souvent considéré comme insuffisant. L’implantation d’un modèle de collaboration qui intègre les physiothérapeutes aux cliniques d’enseignement pourrait améliorer la formation des médecins résidents. Cet article décrit un modèle développé dans une clinique d’enseignement en médecine familiale en examinant les activités interprofessionnelles d’éducation et de collaboration implantées dans ce modèle. Le modèle a permis d’offrir des services de physiothérapie, d’impliquer le physiothérapeute dans la formation des médecins résidents et d’améliorer la collaboration interprofessionnelle, particulièrement pour la prise en charge des personnes ayant des troubles musculosquelettiques.